Prevalence of HIV P24 Antigen; A Sensitive Marker among Seronegative Antibody Blood Donors in Some Hospitals Within Kaduna Metropolis, Nigeria - Fauziyya Adamu; K Abdulfatai; F Musa (UMYU Journal of Microbiology Research)
Detecting and monitoring HIV infection is crucial for effective disease management. The p24 antigen serves as an early viral marker in HIV diagnosis. Despite advancements in diagnosis and monitoring, there is a need for a comprehensive assessment of p24 antigen prevalence in HIV cases. Therefore, this study aims to ascertain the prevalence of p24 antigen among a diverse population of blood donors in Kaduna metropolis. The study recruited 261 blood donors aged between 18 and 55 from various blood bank units in the metropolis. Initial HIV status determination utilized the Immune-Chromatographic Determine® HIV rapid test kit, followed by re-screening with UnigoldRecombigen HIV 1 and 2, boasting 99.70% specificity and 100% sensitivity. HIGHTOP (HIV) ELISA test kit was employed to screen HIV antibodynegative blood donors for HIV p24 antigen. Additionally, demographic factors like gender, residency, age, and marital status were taken into account. Results indicated p24 antigen detection in 9 out of 261 blood samples, yielding a prevalence of 3.5%. Conversely, 252 samples tested negative for the antigen, resulting in a prevalence of 96.5%. The study's findings support the assertion that HIV p24 antigen serves as a sensitive marker, advocating for its integration into routine blood donor screening within Kaduna metropolis to enhance HIV infection detection rates.